A Queue Management Model On Router of Active Network - Lemeshko, O.; Ali Salem Ali; Simonenko, O. (My University, 2015)
The approach to simulation of queue management processes on nodes of an active network is proposed. The model is presented by a triplanar transportation problem of linear programming. The area of the model application is Next Generation Networks that function on the basis of active technologies.
Keywords: Queue; Management; Active Network; Flow